2019
DOI: 10.1371/journal.pone.0215371
|View full text |Cite
|
Sign up to set email alerts
|

Quality of delivery of “right@home”: Implementation evaluation of an Australian sustained nurse home visiting intervention to improve parenting and the home learning environment

Abstract: Background Home visiting programs are implemented in high income countries to improve outcomes for families with young children. Significant resources are invested in such programs and high quality evaluations are important. In the context of research trials, implementation quality is often poorly reported and, when reported, is variable. This paper presents the quality of implementation of the right@home program, a sustained nurse home visiting intervention trialled in Australia, and delivered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 32 publications
(62 reference statements)
2
43
0
1
Order By: Relevance
“…Thirty‐one publications including two reviews met inclusion criteria. These studies identified seven SNHV programs: the Family Nurse Partnership (FNP; Corbacho et al., 2017; Owen‐Jones et al., 2013; Robling et al., 2016); Maternal Early Childhood Sustained Home visiting program (MECSH; Kemp et al., 2007, 2008, 2011, 2013); Minding the Baby (MtB; Ordway et al., 2014, 2018; Sadler et al., 2013; Slade et al., 2005, 2019); Pro Kind (Brand & Jungmann, 2012, 2014; Jungmann et al., 2009, 2015; Sandner et al., 2018; Sandner & Jungmann, 2017; Sierau et al., 2016); right@home (Goldfeld et al., 2017, 2018, 2019; Kemp et al., 2019); VoorZorg (Mejdoubi et al., 2011, 2013, 2014, 2015); and Nurse Family Partnership (NFP; Kitzman et al., 1997; Miller, 2015; Olds, 2008; Olds et al., 1986, 2002). Note that journal articles published prior to 2008 were selected only in cases where these were cited by studies meeting the inclusion criteria and considered necessary for ascertaining program componentry.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty‐one publications including two reviews met inclusion criteria. These studies identified seven SNHV programs: the Family Nurse Partnership (FNP; Corbacho et al., 2017; Owen‐Jones et al., 2013; Robling et al., 2016); Maternal Early Childhood Sustained Home visiting program (MECSH; Kemp et al., 2007, 2008, 2011, 2013); Minding the Baby (MtB; Ordway et al., 2014, 2018; Sadler et al., 2013; Slade et al., 2005, 2019); Pro Kind (Brand & Jungmann, 2012, 2014; Jungmann et al., 2009, 2015; Sandner et al., 2018; Sandner & Jungmann, 2017; Sierau et al., 2016); right@home (Goldfeld et al., 2017, 2018, 2019; Kemp et al., 2019); VoorZorg (Mejdoubi et al., 2011, 2013, 2014, 2015); and Nurse Family Partnership (NFP; Kitzman et al., 1997; Miller, 2015; Olds, 2008; Olds et al., 1986, 2002). Note that journal articles published prior to 2008 were selected only in cases where these were cited by studies meeting the inclusion criteria and considered necessary for ascertaining program componentry.…”
Section: Resultsmentioning
confidence: 99%
“…All programs appear to offer at least three prenatal visits and most include weekly visits in the first 4–6 weeks following birth, with frequency of visits tapering out at different rates thereafter. It is worth noting that the right@home trial reported very high rates of uptake (97% commencement), completion (87% to child age 2 years), and engagement (72% received 75% of scheduled visits; Kemp et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations